PROBLEM PEMBELAJARAN BERDIFERENSIASI BERBASIS PROFIL BELAJAR DALAM PEMBELAJARAN SEJARAH DI SMAN 2 MOJOKERTO - Achmad Dicky Setyawan; Agus Suprijono; Dety Purwantini (Inteligensi : Jurnal Ilmu Pendidikan, 2023)
This research aims to describe the application, solution and management of differentiated learning problems based on student learning profiles in History subjects. This study used qualitative research methods with data analysis using data reduction, data presentation, and drawing conclusions which were carried out continuously. The results and discussion obtained were the application of differentiated learning in History subjects using a differentiation strategy consisting of content, process, and product. The resulted of the research in the form of differentiated learning based on student learning profiles can be used in limited resources, educator skills, limited time, different assessments, and complex classroom management. This can be applied to a variety of different learning characteristics of students by fulfilling all the needs of students based on their abilities and taking into account the learning readiness of students so as to raise the learning motivation of each student in the history learning process in class.